2012
DOI: 10.1177/1088868312440046
|View full text |Cite
|
Sign up to set email alerts
|

When Death is Good for Life

Abstract: Research derived from terror management theory (TMT) has shown that people's efforts to manage the awareness of death often have deleterious consequences for the individual and society. The present article takes a closer look at the conceptual foundations of TMT and considers some of the more beneficial trajectories of the terror management process. The awareness of mortality can motivate people to enhance their physical health and prioritize growth-oriented goals; live up to positive standards and beliefs; bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(80 citation statements)
references
References 169 publications
(191 reference statements)
3
76
0
1
Order By: Relevance
“…Clearly, sports performance is also often motivated by approach-oriented motives such as growth, competence, and self-expansion (e.g., Pelletier, Fortier, Vallerand, & Brière, 2001;Vallerand, 2004). Theorists and researchers have considered the interplay of the defensive motivation posited by TMT and the more growthoriented motivation posited by self-determination (e.g., Greenberg, Pyszczynski, & Solomon, 1995;Vail et al, 2012) and have suggested that any given behavior could be driven entirely by defensive concerns, entirely by growth motivation, or by a combination of the two. For example, in the sports domain, an athlete could be motivated entirely to prove worth to self or others, to gain a lasting legacy in the sport, or to enjoy challenging oneself, growing, and becoming the best they can be at the sport, or (probably most often) by a combination of these motivations.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, sports performance is also often motivated by approach-oriented motives such as growth, competence, and self-expansion (e.g., Pelletier, Fortier, Vallerand, & Brière, 2001;Vallerand, 2004). Theorists and researchers have considered the interplay of the defensive motivation posited by TMT and the more growthoriented motivation posited by self-determination (e.g., Greenberg, Pyszczynski, & Solomon, 1995;Vail et al, 2012) and have suggested that any given behavior could be driven entirely by defensive concerns, entirely by growth motivation, or by a combination of the two. For example, in the sports domain, an athlete could be motivated entirely to prove worth to self or others, to gain a lasting legacy in the sport, or to enjoy challenging oneself, growing, and becoming the best they can be at the sport, or (probably most often) by a combination of these motivations.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the experience of mortality may shift preferences toward goals with intrinsic meaning (such as interpersonal connection and community development) rather than extrinsic goals (such as amassing wealth and status) (Vail et al 2012). The logic suggests that among other things, a renewed investment in family will emerge in response to an awareness of human frailty (Fritsche et al 2007; Nakonezny et al 2004).…”
Section: Fertility In Response To Mortality: Theorymentioning
confidence: 99%
“…In this sense, MS could even have positive consequences by MORTALITY SALIENCE AND REGRET -25 -helping the individual not to worry too much about past events. Accordingly, it has been shown that under certain conditions, MS can enhance creativity, innovation, the exploration of novel alternatives as well as flexible cognitive structures (for an overview, see Vail et al, 2012).…”
Section: Benefits Of (Not) Experiencing Regretmentioning
confidence: 99%